PENERAPAN ALGORITMA MD5 SEBAGAI PENGAMAN AKUN PADA APLIKASI WEB EMUSRENBANG KOTA BINJAI - KADRI YUSUF (STMIK KAPUTAMA, 2020)
Encryption is a technique for hiding passwords into writing that changes from their original form. Encryption aims to increase the security of passwords on an account so that it is not misused by people who are not responsible or who have an interest in seeing data on the application or the web. Emusrenbang application in Binjai City is a website that aims to accommodate community proposals in Binjai so that every community in Binjai city can submit proposals without having to come to the Kelurahan office. Each community has an account to be able to submit proposals based on Local Government Work Plans (OPD). To increase security for each user account is equipped by adding a password. To prevent passwords from being read easily, passwords are encrypted using the MD5 algorithm implemented in PHP. MD5 is an algorithm. It is expected that the emusrenbang web application can cut costs in implementing the emusrenbang from villages, sub-districts, the Regional Representative Council and the Regional Parliament Council (PokD), and can increase public trust with government transparency in carrying out musrenbang in the city of Binjai. Keywords: Cryptography, MD5 Algorithm